A novel approach for direct conversion of wind energy to heat utilizing a hydraulic medium for domestic heating applications. (November 2022) - Iyer, Kaushikk Ravender; Roozbahani, Hamid; Alizadeh, Marjan; Handroos, Heikki
Abstract: The objective of this research was to investigate utilizing small to medium-scale wind energy in domestic heating without considerable losses by direct conversion of the wind energy to thermal energy through a hydraulic medium. For this purpose, the virtual wind turbine mathematical model was developed in Simulink. Using hardware-in-the-loop (HIL) simulation, the Simulink model was integrated with dSPACE to control the AC motor connected to a variable displacement pump. The speed of the motor was controlled using a frequency converter, to which the torque of the virtual turbine model was supplied in real-time, and the angular velocity of the motor was fed back to the system. By regulating the valve orifice, a pressure drop was created across the orifice area, which led to the generation of thermal power. In order to validate the real-time simulated turbine, the output power and the characteristic curve of the tip speed ratio ( λ ) based on the power coefficient ( C P ) resulted from the real-time simulation were reconciled with the corresponding curves of the real turbine. The results demonstrated the conformity of the real-time simulation with the real turbine. The thermal power produced was measured by measuring the temperature of the hydraulic oil. Highlights: Direct conversion of wind energy to thermal power through a hydraulic medium. Novel approach for domestic heating applications. Reduced losses by direct conversion of wind energy to heat via a hydraulic medium. Beneficial for places with intense wind power and inaccessible electricity grid.